Epidemiological profile of confirmed meningitis cases reported in the state of Ceará from 2014 to 2018 (Research, Society and Development, 2020)
Meningitis is an inflammatory process that affects the brain membranes (pia mater and arachnoid), and cerebrospinal fluid (CSF). Such a process can be caused by viruses and bacteria. The aim of this study was to analyze the epidemiological profile of cases of meningitis in the state of Ceará, reported from 2014 to 2018. This is a cross-sectional, exploratory study that outlined a quantitative and descriptive study on cases of meningitis in the state of Ceará. Ceará, retrospectively, from 2014 to 2018. Data from the Department of Informatics of SUS, DATASUS, were used. Of the 1710 reported cases of meningitis, the highest prevalence was in the 20-39 age group and the 40-59 age group, 32.0% and 20.6%, respectively. Males account for 62% of confirmations. 1398 occur in the state capital, Fortaleza, being of majority expression. The diagnostic test with the highest number of confirmations is the chemocytological test.